Morphological and Seroprevalence of Canine Babesiosis - Zahraa Akram Saleh, Dalia Ahmed kalef (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Babesia species are parasitic microorganisms that invade the red blood cells of various mammals, causing Babesiosis. Babesia canis and Babesia gibsoni infect dogs and notably responsible for canine Babesiosis. This study first Seroprevalence of canine babesiosis in Baghdad, Iraq Objectives: This study aimed to establish the incidence of Babesia spp. in dog populations within Baghdad City, Iraq, and to identify the epidemiological risk factors associated with canine Babesiosis Methods: The study extended from November 2023 to May 2024, and involved 228 blood samples collected from numerous dog breeds across different regions of Baghdad. Blood samples were examined using Giemsa and Acridine Orange stains, ELISA, and immunochromatographic tests to detect the Babesia parasite. Statistical analysis of the prevalence rates affording the age, gender, breed of dogs, and their geographic districts. Results: The study revealed a higher incidence of Babesia gibsoni 44% to Babesia canis35%, with total infection rates peaking in warmer months. Stray dogs exhibit the highest infection rate 33.3% of dog babesiosis in contrast to other breeds. exhibited the highest infection rates33.3%. Conclusion: The current study provides important information on the epidemiology of canine babesiosis from Baghdad, Iraq.